Catatan Kelam dari Rentetan Kasus Tawuran antar Remaja di Kota Padang: Melihat Eksistensi Layanan Bimbingan Konseling dalam Upaya Penyelesaian - Putra; Syaiful Adnan; Maturidi (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
This paper was born from anxiety over the rampant brawls between teenagers in Padang City. This has a significant impact on all aspects of human life, from fear and anxiety when traveling at night, parental anxiety about their children's social interactions, deviant behavior, and other negative impacts. The rampant brawls add to the dark record of crime in Padang City, requiring serious attention from all levels of society, especially the authorities, to take decisive action to eradicate this brawl problem. The author conducted this paper using a library research method, where in seeking and refining the answers to this research through accurate sources, including books, journal articles, and other valid sources. The results of this study found that: first, the problem of brawls has occurred from previous years, where in this paper the author began to compile data from 2021-2025, second, brawls have a very serious impact, meaning this problem really falls into the category of deviation and crime, third, several services in the science of guidance and counseling are able to contribute and strive for how this problem of brawls can be prevented and eradicated which in this case can be practiced directly by certain parties, such as BK teachers in schools, social volunteers and clergy in community institutions. It is hoped that the problem of brawls between teenagers in Padang City can be resolved even though faced with various obstacles and barriers